Reinvesting in African Small-Holder Agriculture : The Role of Tree Crops in Sustainable Farming Systems - World Bank (Washington, DC, 2013)
This Policy and Strategy Paper contributes to an ongoing policy debate-within the Bank but also with its client governments-about the role of tree crops in various production systems, and as key commodities in the trade portfolio of various African nations. It attempts to answer the following questions: a) What is the role of tree crops in a rural development strategy focused on smallholders? B) Under what conditions can small-holder tree crops be included in such a strategy, and be viable, and what are the operational guidelines to do so? The set of tree crops considered includes cashew nuts, coconuts, cocoa, coffee, gum arabic, oil palm, rubber, and tea. Other tree crops, such as teak and tropical fruit, hold less economic importance for the subcontinent, and are thus excluded from the analysis. Although plantations exist for many of these crops, small-holders play a major role in their overall production. These small-holder systems are mixed farming systems, including a variety of annual crops as well as major, or minor tree crops. The paper illustrates the place of tree crops in African economies, at the macro- and micro-levels, and draws a number of lessons from a set of Asian experiences. It then suggests that, under appropriate conditions, investment in small-holder systems that include tree crops can be a good choice for investment in the productive sector. The report finally provides strategic and operational guidelines, and, includes five sections: 1. Background; 2. Support to the Sector; 3. The Asian Experience(s); 4. Perspectives on Tree Crops; and, 5. Strategic and Operational Issues. A bibliography is included, and the Statistical Appendix is available both as a separate document, and electronically.